2017
DOI: 10.3389/fcimb.2017.00192
|View full text |Cite
|
Sign up to set email alerts
|

Identification of S-Nitrosylated (SNO) Proteins in Entamoeba histolytica Adapted to Nitrosative Stress: Insights into the Role of SNO Actin and In vitro Virulence

Abstract: We have recently reported that Entamoeba histolytica trophozoites can adapt to toxic levels of the nitric oxide (NO) donor, S-nitrosoglutathione (GSNO). Even if the consequences of this adaptation on the modulation of gene expression in NO-adapted trophozoites (NAT) have been previously explored, insight on S-nitrosylated (SNO) proteins in NAT is missing. Our study aims to fill this knowledge gap by performing a screening of SNO proteins in NAT. Employing SNO resin-assisted capture (RAC), we identified 242 put… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…We have previously reported that OS induced by H 2 O 2 inhibits protein synthesis in E. histolytica (Shahi et al, ; Trebicz‐Geffen et al, ). The presence of proteins that are involved in translation among OXs, such as the elongation factor‐1 alpha and elongation factor 2, suggests that AF regulates the translation of proteins in the AF‐treated trophozoites.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…We have previously reported that OS induced by H 2 O 2 inhibits protein synthesis in E. histolytica (Shahi et al, ; Trebicz‐Geffen et al, ). The presence of proteins that are involved in translation among OXs, such as the elongation factor‐1 alpha and elongation factor 2, suggests that AF regulates the translation of proteins in the AF‐treated trophozoites.…”
Section: Resultsmentioning
confidence: 96%
“…Lane 1: Untreated control trophozoites, Lane 2: trophozoites treated with 10‐μg ml −1 puromycin for 20 min, Lane 3: Trophozoites treated with 1.5‐μM AF for 24 hr and then labelled with 10‐μg ml −1 puromycin for 20 min, Lane 4: Trophozoites treated with 2.5 μM H 2 O 2 for 30 min and then treated with puromycin for 20 min, Lane 4: Trophozoites treated with cycloheximide (100 μg ml −1 ) for 5 min and then treated with puromycin for 20 min. The protein extracts were separated by denaturing electrophoresis and analysed by immunoblotting with a monoclonal puromycin antibody 12D10 clone as previously described (Trebicz‐Geffen et al, )…”
Section: Resultsmentioning
confidence: 99%
“…The cytopathic activity of E . histolytica trophozoites was determined using a previously described protocol [ 84 ].…”
Section: Methodsmentioning
confidence: 99%
“…Motility is an essential function for the survival of E. histolytica [ 67 , 68 ] not only for displacement and phagocytosis of host cells, but also for the intracellular trafficking of virulence factors [ 69 ]. Another project correlating the transcriptomic data of NO-exposed parasites to the proteomic data of NO-adapted trophozoites [ 70 ] showed an up-regulation in the gene expression of cytoskeleton proteins that were previously identified by proteomics. Mammalian actin S -nitrosylation can decrease actin polymerization and rearrange its cytoskeleton.…”
Section: E Histolytica Endomembrane Network Ismentioning
confidence: 99%
“…Mass spectrometry analysis of NO-adapted proteins showed that the E. histolytica actin residue Cys286 was S -nitrosylated, suggesting that it could indeed impair the cytoskeleton functions in E. histolytica . These NO-adapted trophozoites had reduced virulence functions (i.e., erythrophagocytosis, cytophatic activity, and motility), similar to when actin is inhibited by Cytochalasin D, suggesting that NO exposure not only affects the endomembrane network [ 25 ], but also the cytoskeleton functions [ 70 ] by increasing its gene expression profile and modifying the proteins. Interestingly, once the NO pressure is removed, the trophozoites regained the same levels of virulence functions as the control parasites [ 70 ], demonstrating once again the ability of the amoeba to quickly adapt to different environments.…”
Section: E Histolytica Endomembrane Network Ismentioning
confidence: 99%